2022
DOI: 10.3389/fpsyg.2022.807621
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Model for the Establishment of the Hospice Care Delivery System for Iranian Adult Patients With Cancer

Abstract: IntroductionMaking appropriate plans for the provision of hospice care is considered a perceived need in the Iranian health system. The current study aimed to develop a model for establishing hospice care delivery system for the adult patients with cancer.Materials and MethodsThis study is part (data of the third and fourth phases) of a larger study that has been done in four phases. This Health System Policy Research (HSPR) utilized a mixed qualitative-quantitative approach. At the first phase, a qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In one study found that Muslim people put off uncomfortable conversations about care planning until they become ill or suddenly become unable to express their wishes [ 18 ]. Despite the interesting of Muslim community in learning and receiving the concept of ACP [ 19 ], ACP in Iran, does not exist in a coherent way, but researchers and clinician have separately and limitedly investigated the dimensions of it, including palliative care [ 10 , 20 ] and hospice care [ 15 , 21 ], preferred place of care and preferred place of death [ 11 ], have a kind of ADs as Vasiyyah [ 22 ], and do not resuscitation [ 23 ] in their practice and research [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one study found that Muslim people put off uncomfortable conversations about care planning until they become ill or suddenly become unable to express their wishes [ 18 ]. Despite the interesting of Muslim community in learning and receiving the concept of ACP [ 19 ], ACP in Iran, does not exist in a coherent way, but researchers and clinician have separately and limitedly investigated the dimensions of it, including palliative care [ 10 , 20 ] and hospice care [ 15 , 21 ], preferred place of care and preferred place of death [ 11 ], have a kind of ADs as Vasiyyah [ 22 ], and do not resuscitation [ 23 ] in their practice and research [ 24 ].…”
Section: Introductionmentioning
confidence: 99%